2000
DOI: 10.1002/1522-726x(200010)51:2<234::aid-ccd22>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Coronary rotational atherectomy via transradial approach: A study using radial artery intravascular ultrasound

Abstract: The use of coronary rotational atherectomy via radial artery (RA) has been limited because of the large diameter of guiding catheters. We studied the feasibility of this approach by sizing the RA by intravascular ultrasound (IVUS) and using 7 Fr (2.31 mm) guiding catheters. Seventeen transradial percutaneous transluminal coronary rotational atherectomy (PTCRA) procedures were performed in 16 patients, mean age 62 +/- 12 years, for a total of 19 vessels treated. The mean RA diameter was 2.9 +/- 0.36 mm and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…In the series of Gioia et al 28 where it was shown that PCI with rotational atherectomy was feasible and safe via transradial access, among the 16 patients there was 1 protected LMCA rotational atherectomy and only 1 case that was performed with a 6 French guiding catheter whereas the remainder were carried out with a 7 French system. Egred et al 29 presented 28 cases of transradial rotational atherectomy PCIs with mean age of 71 AE 9.4 years but there was no LMCA disease.…”
Section: Discussionmentioning
confidence: 99%
“…In the series of Gioia et al 28 where it was shown that PCI with rotational atherectomy was feasible and safe via transradial access, among the 16 patients there was 1 protected LMCA rotational atherectomy and only 1 case that was performed with a 6 French guiding catheter whereas the remainder were carried out with a 7 French system. Egred et al 29 presented 28 cases of transradial rotational atherectomy PCIs with mean age of 71 AE 9.4 years but there was no LMCA disease.…”
Section: Discussionmentioning
confidence: 99%
“…Another issue is regarding the utilization of devices requiring catheters with a larger inner diameter (7-F to 8-F or more). No large-scale trials have been conducted, but some studies have shown the feasibility of 7-F to 8-F transradial procedures (46,47) in selected patients by experienced operators. Of course, these are pioneering reports, and further evaluation is needed with large-scale trials, but technologic improvements associated with increased operator skills may lead to the utilization of transradial access in always more challenging situations without significant harm to patients (48).…”
Section: Discussionmentioning
confidence: 99%
“…The safety of transradial access with devices requiring catheters with a larger internal diameter (7F or greater) need to be evaluated in large trials. Initial results are encouraging in selected patients by experienced operators 15–18 …”
Section: Comparison With the Transfemoral Approachmentioning
confidence: 94%
“…Initial results are encouraging in selected patients by experienced operators. [15][16][17][18] The procedural failure is rare with modern practice, experience, and availability of the new equipment. There could be several reasons for procedural failure: Firstly, there may be failure to successfully puncture and cannulate the radial artery, because of the small vessel size, tortousity, or spasm.…”
Section: Comparison With the Transfemoral Approachmentioning
confidence: 99%